Perspectives From the 12th Annual Minipig Research Forum: Early Inclusion of the Minipig in Safety Assessment Species Selection Should be the Standard Approach. (October 2019) - Jones, Keith; Harding, Joanna; Makin, Andy; Singh, Pramila; Jacobsen, Björn; Mikkelsen, Lars Friis
Over the last decade, the minipig has been established as a species which can be used in biomedical research, including drug development safety assessment. There are no mandatory regulatory guidelines regarding species selection strategy for safety assessment; hence, choice is at the discretion of companies responsible for drug development. A survey of member companies by IQ DruSafe (2016) highlighted inconsistent and low use of the minipig. At the 12th Annual Minipig Research Forum in 2018, presentations and a workshop examined current practices and considered if the minipig could be utilized more from earliest drug development stages. Despite the agreed utility of scientific data and validity of the minipig, especially for small molecules, each company has its own approach in nonrodent species selection, without consistent rationale. The overall objective should be to ensure the most appropriate species is selected and is scientifically based, with the minipig systematically included from early screening stages.